2005
DOI: 10.1111/j.1600-6143.2005.01080.x
|View full text |Cite
|
Sign up to set email alerts
|

BK Virus‐Specific Antibodies and BKV DNA in Renal Transplant Recipients with BKV Nephritis

Abstract: We evaluated twenty renal transplant subjects at various stages of BKV nephritis (BKVN) for BKV-specific IgG and IgM antibodies using ELISA technique and BKV-DNA using PCR. They were divided as early onset (n = 7), stabilizing (n = 3), resolved (n = 8) and late onset (n = 2) BKVN. BKV-specific antibodies and BKV-DNA were simultaneously determined. The mean BKV-specific IgG level in early onset and stabilizing BKVN were 64 and 39 EIA units, and were significantly lower than 138 EIA units seen in resolved BKVN, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 21 publications
5
64
0
Order By: Relevance
“…An increasing anti-BK antibody titer has been seen to develop with a decrease of immunosuppression and treatment of BKVN (17). However, high-titer anti-BK antibody in the donor has been associated with an increased likelihood of development of BK viruria and viremia in the recipient (18).…”
Section: Risk Factors For Infectionmentioning
confidence: 99%
“…An increasing anti-BK antibody titer has been seen to develop with a decrease of immunosuppression and treatment of BKVN (17). However, high-titer anti-BK antibody in the donor has been associated with an increased likelihood of development of BK viruria and viremia in the recipient (18).…”
Section: Risk Factors For Infectionmentioning
confidence: 99%
“…While IgG monitoring was not routinely performed in our cohorts it is plausible that depletion of BK or other viral-specific IgG, may have occurred. Previous data demonstrated that low BK virus IgG levels correlated with a higher degree of BK replication [27]. BK and other non-CMV viral infections seen in our cohort either lacked prophylactic strategies (i.e., JC virus, RSV) or occurred late (>6 months) after RTX exposure, making prevention and/or monitoring for these infections difficult.…”
Section: Discussionmentioning
confidence: 73%
“…Hariharan et al (2005) found that mean BK virus-specific IgG levels in patients with early onset and stabilizing BK virus nephropathy were significantly lower than those seen after the disease had resolved. Mean plasma BK virus load declined over the same period.…”
Section: Sirmentioning
confidence: 95%